Correlation analysis of serum Glycosylphosphatidylinositol Mannosyltransferase 1 (GMP1) levels in type 2 diabetes mellitus: GMP1 in type 2 diabetes mellitus - Yang, Xiaolin; Wang, Qichang; Wei, Chen; Zhao, Jian (Journal of Medical Biochemistry, 2025)
Objective: To investigate the serum expression of Glycosylphosphatidylinositol Mannosyltransferase 1 (GMP1) in type 2 diabetes mellitus (T2DM) patients and its correlation with hypertriglyceridemia (HTG) to shed light on lipid metabolism disorders in T2DM.Methods: A total of 239 subjects were included, among whom 92 patients were in the T2DM combined with HTG group and 147 patients were in the T2DM without HTG group. The concentration of the serum GMP1 protein was quantitatively detected via enzyme-linked immunosorbent assay (ELISA). Moreover, the levels of serum triglycerides (TGs) and other related metabolic indicators (such as blood glucose, glycated hemoglobin (HbA1c), total cholesterol, and high/low-density lipoprotein cholesterol) were detected via conventional biochemical methods. To evaluate the potential impact of GMP1 on the occurrence of T2DM combined with HTG.Results: Both the DM group and the DM+HTG group had significantly higher serum GMP1 levels (P
Keywords: Glycosylphosphatidylinositol Mannosyltransferase 1 (GMP1); Hypertriglyceridemia (HTG); Diabetes disease